Noncanonical roles of ATG5 and membrane atg8ylation in retromer assembly and function - Masroor Ahmad Paddar; Fulong Wang; Einar S Trosdal; Emily Hendrix; Yi He; Michelle R Salemi; Michal Mudd; Jingyue Jia; Thabata Duque; Ruheena Javed; Brett S Phinney; Vojo Deretic (eLife)
ATG5 is one of the core autophagy proteins with additional functions such as noncanonical membrane atg8ylation, which among a growing number of biological outputs includes control of tuberculosis in animal models. Here, we show that ATG5 associates with retromer’s core components VPS26, VPS29, and VPS35 and modulates retromer function. Knockout of ATG5 blocked trafficking of a key glucose transporter sorted by the retromer, GLUT1, to the plasma membrane. Knockouts of other genes essential for membrane atg8ylation, of which ATG5 is a component, affected GLUT1 sorting, indicating that membrane atg8ylation as a process affects retromer function and endosomal sorting. The contribution of membrane atg8ylation to retromer function in GLUT1 sorting was independent of canonical autophagy. These findings expand the scope of membrane atg8ylation to specific sorting processes in the cell dependent on the retromer and its known interactors.